2017
DOI: 10.1016/j.ebiom.2017.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CD147 for T to NK Lineage Reprogramming and Tumor Therapy

Abstract: CD147 is highly expressed on the surface of numerous tumor cells to promote invasion and metastasis. Targeting these cells with CD147-specific antibodies has been validated as an effective approach for lung and liver cancer therapy. In the immune system, CD147 is recognized as a co-stimulatory receptor and impacts the outcome of thymic selection. Using T cell-specific deletion, we showed here that in thymus CD147 is indispensable for the stable αβ T cell lineage commitment: loss of CD147 biases both multipoten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…Previously, we reported that CD147 depletion in T cells resulted in deficient thymic development and that both the size and the weight of the thymus were less in the CD147 T-KO mice than they were in the wild-type mice 6 weeks after birth. 33 Interestingly, with the extension of our observation time, we found that the weight of and T-cell number in the thymus in the CD147 T-KO mice and wild-type mice were found to be similar 12 weeks after birth (Fig. 1a–c ).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Previously, we reported that CD147 depletion in T cells resulted in deficient thymic development and that both the size and the weight of the thymus were less in the CD147 T-KO mice than they were in the wild-type mice 6 weeks after birth. 33 Interestingly, with the extension of our observation time, we found that the weight of and T-cell number in the thymus in the CD147 T-KO mice and wild-type mice were found to be similar 12 weeks after birth (Fig. 1a–c ).…”
Section: Resultsmentioning
confidence: 59%
“… 30 32 In our previous studies, we found that, in young mice, CD147 depletion in thymocytes (CD147 T-KO ) resulted in decreased thymus size, thymic cellularity loss, and diminished T-cell lineage cell numbers, which were accompanied by increases in the number of various lymphocyte populations with innate immunological functions, such as γδ T cells, NKT-like cells, and NK-like cells. 33 In another interesting finding, the size and weight of the thymus in CD147 T-KO mice decreased more slowly than did those in wild-type mice during aging. This result indicates that CD147 on T cells may be involved in thymic involution.…”
Section: Introductionmentioning
confidence: 94%
“…Previously, we reported that the early deletion of CD147 expression in thymocytes (CD147 T-KO mice [ 24 ]) leads to the enrichment of lymphocytes with innate features [ 22 ]. Moreover, in these CD147 T-KO mice, while Treg development in the thymus appeared to be normal, the ratio of Foxp3+ Tregs was reduced in peripheral organs, including lymph nodes, spleen, and circulating blood (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of CD147 T-KO mice on the C57Bl/6 background have been previously published [ 22 ]. Wild-type (WT) female C57BL/6 mice were purchased from the Fourth Military Medical University, Laboratory Animal Center, and white C57BL/6 mice were obtained from the Biomedical Analysis Center of the Third Military Medical University.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, NK cells become confused to act as stimulatory immune cells or exert immunosuppressive action in the event of a cytokine storm seen in severe COVID-19 patients. However, NK cells express CD147, another receptor for SARS-CoV2 entry, and also possess a functional renin-angiotensin system (RAS) [196,197]. Thus SARS-CoV2 virus can infect NK cells, but antiviral IFN-based and cytokine-based immune responses do not take place to counter the pathogen due to the viral strategies of hijacking.…”
Section: Immunometabolic Reprogramming Among Dcs and Nk Cells During mentioning
confidence: 99%